Development of Media Solting as A Suport of Accurate Shooting at SSB AB Perkasa - Wahyu Agung Prasetyo; Slamet Junaidi; M. Anis Zawawi (CV. Nusantara Sporta, 2023)
Football is very popular with the public so that many people want to make it a profession to become a professional player by mastering the basic techniques in it, especially shooting skills which are considered important. To achieve this is inseparable from a development tool. Therefore the researchers made observations at SSB AB Perkasa which showed that the trainers had not used assistive devices in delivering the material so this study aimed 1) to find out the development of media solting as a support for shooting accuracy at SSB AB Perkasa, 2) to find out the validity of developing media solting as a support accuracy of shooting at SSB AB Perkasa, 3) to find out the practicality of developing media solting as a support for shooting accuracy at SSB AB Perkasa, and 4) to determine the effectiveness of media solting as a support for shooting accuracy at SSB AB Perkasa. This study uses the Sugiyono development procedure which is a modification of Borg and Gall by using 9 stages of the 10 existing steps. The conclusions of this study 1. The solting media is rectangular in shape divided into 3 square parts which have different colors, 2. The solting media is said to be valid because it obtains a percentage of 80%, 3. The solting media is said to be practically operable because it has a percentage of 80%, 4. Solting media can be used effectively because it has a score of 95%